Eukaryotic translation initiation factor 3B downregulation inhibits cell proliferation and promotes cell apoptosis through negatively regulating tumor necrosis factor receptor superfamily member 21 in gastric cancer - Xiong, Huiling; Hu, Mei; Huang, Hui; Gong, Jing; Wu, Jie; Zhang, Heng (Translational Cancer Research, 2019)
Background: This study aimed to detect eukaryotic translation initiation factor 3B (EIF3B) expression in gastric cancer (GC) cell lines, and further explore the effect of EIF3B downregulation on GC cell proliferation and apoptosis. Methods: EIF3B mRNA expression and protein expression in human GC cell lines (NCI-N87, AGS, HGC-27, BGC-823 and MGC80-3) and human gastric mucosal epithelial cell line (GES-1) were detected. Control siRNA (Si-NC group) and EIF3B siRNA (Si-EIF3B group) were transfected into NCI-N87 cells. Rescue experiment was performed by transfection of EIF3B siRNA (Si-EIF3B group) and EIF3B siRNA plus tumor necrosis factor receptor superfamily member 21 (TNFRSF21) siRNA (Si-EIF3B & Si-TNFRSF21 group) into NCI-N87 cells. Besides, cell proliferation, apoptosis, TNFRSF21 expression and TRAF1 expression were assessed. Results: EIF3B mRNA expression and protein expression were elevated in NCI-N87, AGS, HGC-27 and BGC-823 cell lines compared to GES-1 cell line. In NCI-N87 cells, proliferation was reduced in Si-EIF3B group compared to Si-NC group. For cell apoptosis, its rate and apoptotic marker C-Caspase 3 expression were increased but anti-apoptosis marker Bcl-2 expression was reduced in Si-EIF3B group compared to Si-NC group. Moreover, mRNA expression and protein expression of TNFRSF21 were increased in Si-EIF3B group compared to Si-NC group, while mRNA expression and protein expression of TRAF1 were reduced in Si-EIF3B group compared to Si-NC group. In rescue experiment, cell proliferation was increased but apoptosis was decreased in Si-EIF3B & Si-TNFRSF21 group compared to Si-EIF3B group. Conclusions: EIF3B is overexpressed in GC cell lines, and its downregulation inhibits cell proliferation while promotes apoptosis through negatively regulating TNFRSF21 in GC.